The mighty Miss Malone - Curtis, Christopher Paul. (Wendy Lamb Books, 2012)
With love and determination befitting the "world's greatest family," twelve-year-old Deza Malone, her older brother Jimmie, and their parents endure tough times in Gary, Indiana, and later Flint, Michigan, during the Great Depression.